2005
DOI: 10.1111/j.1399-0039.2005.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 5q candidate genes in coeliac disease: Genetic variation at IL4, IL5, IL9, IL13, IL17B and NR3C1

Abstract: Genetic predisposition to coeliac disease (CD) is determined primarily by alleles at the HLA-DQB locus, and evidence exists implicating other major histocompatibility complex-linked genes (6p21) and the CTLA4 locus on chromosome 2q33. In addition, extensive family studies have provided strong, reproducible evidence for a susceptibility locus on chromosome 5q (CELIAC2). However, the gene responsible has not been identified. We have assayed genetic variation at the IL4, IL5, IL9, IL13, IL17B and NR3C1 (GR) loci,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
(57 reference statements)
1
13
0
1
Order By: Relevance
“…Previous studies have compared treated and potential patients with CD and have reported IL-17 elevation in the mucosa of untreated patients (14,15). However, Ryan et al (16) examined the relation between IL-17 polymorphisms and CD and showed no relation between IL-17 (762 C/A, 1586 A/G, and 6769 A/G) polymorphisms and CD. Espinoza et al (17) showed that the IL-17A 197A allele correlates to more efficient IL-17 production.…”
mentioning
confidence: 98%
“…Previous studies have compared treated and potential patients with CD and have reported IL-17 elevation in the mucosa of untreated patients (14,15). However, Ryan et al (16) examined the relation between IL-17 polymorphisms and CD and showed no relation between IL-17 (762 C/A, 1586 A/G, and 6769 A/G) polymorphisms and CD. Espinoza et al (17) showed that the IL-17A 197A allele correlates to more efficient IL-17 production.…”
mentioning
confidence: 98%
“…[8][9][10][11][12] Such associations are postulated to be a consequence of natural variation in the expression levels of IL-5 or IL5RA and hence the strength of signalling through this pathway. In this study, we have investigated the hypothesis that genetic variation in IL-5 signalling may be associated with the development or severity of FIP1L1-PDGFRA-positive CEL in humans.…”
Section: Introductionmentioning
confidence: 99%
“…There has been no clear association with polymorphisms in many of these genes and celiac disease [24], apart from a significant increase in the frequency of the tumour necrosis factor a (TNF-a) À308A allele and the interferon (IFN-g) 874T allele with the two in combination in 40% versus 22% of controls [25]. A Finnish study [26 ] found no association with polymorphisms in interleukin (IL)-6, IL-10, transforming growth factor b (TGF-b) and IFN-g but an association of TNF-a À308A, although this was not statistically significant.…”
Section: Hla and Non-hla Geneticsmentioning
confidence: 97%